Development of coconut snack bar - Domingo, Maria Liza Paz; De Leon, Sonia Y. (1993)
A granola-type snack food utilizing high percentage of dessicated coconut was studied. Preliminary formulation trials indicated that the snack food should contain oats, pinipig, cashew, raisins, margarine, sugar, glucose, water and cinnamon. Various proportions of dessicated coconut were incorporated to arrive at the right combination which would provide a high level of consumer acceptance. Results indicated that a high proportion of coconut was preferred. Proximate analysis showed that the product is high in crude fiber (19.7%). It had crude protein content of 5.34% crude fat content of 18.63%, total ash of 0.51% and a moisture content of 5.61%. It had a water activity of 0.49. Based on the consumer acceptance test, the snack food was scored "very good" in quality judgement, "like moderately" in effect and "twice a week" for action. Furthermore, a foil packaging material was preferred. Price ranging from P.1.75 to 2.50 was suggested for a 12-gram bar. Production cost estimates and proximate analysis showed that the product can compete with the other health snack foods existing in the market.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coconut products; Snack foods